Estimation of the Band Broadening Parameters in Single Detection Size Exclusion Chromatography: A Comparative Study of Various Column Combinations - Schnöll Bitai, Irene (2007)
Alternative approaches for the determination of band broadening in size-exclusion chromatography based on the use of exponentially modified Gaussian (EMG) functionswere used to experimentally investigate the performance of two different column sets. In both cases, the columns were combined in order to cover the complete fractionation range (from 103 to 5×106 g mol-1), which is of interest in many applications. When analyzing experimental chromatograms the question of proper data treatment (especially the necessary smoothing routines) became obvious and is discussed accordingly. First results indicate that the exponential decay time of the EMG decreases and the standard deviation of its Gaussian component slightly increases (or remains almost constant) with increasing retention volumes. As a consequence, the total variance and the asymmetry of the EMG both decrease with the retention volume. A favorable agreement with independent experimental results (obtained by other researchers on the basis of analyzing ultra narrow standards) was found. Additionally, the skew was also investigated as a function of the retention volume and the trend was found to be in concordance with the predictions of theoretical models. The comparison with theoretical models is also discussed.